2021
DOI: 10.3390/app11041742
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Feature Selection and Forecasting Machine Learning Algorithms for Predicting Glycaemia in Type 1 Diabetes Mellitus

Abstract: Type 1 diabetes mellitus (DM1) is a metabolic disease derived from falls in pancreatic insulin production resulting in chronic hyperglycemia. DM1 subjects usually have to undertake a number of assessments of blood glucose levels every day, employing capillary glucometers for the monitoring of blood glucose dynamics. In recent years, advances in technology have allowed for the creation of revolutionary biosensors and continuous glucose monitoring (CGM) techniques. This has enabled the monitoring of a subject’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 63 publications
0
9
0
1
Order By: Relevance
“…Some machine learning methods have emerged to identify the causal features from the large dataset [ 41 , 42 ]. These could be a new way forward to analyse the current dataset for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Some machine learning methods have emerged to identify the causal features from the large dataset [ 41 , 42 ]. These could be a new way forward to analyse the current dataset for future work.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021, another study [ 27 ] compared different feature selection and forecasting machine learning algorithms for predicting glycemia in type 1 diabetes mellitus. The authors used a dataset of glucose readings collected from patients with type 1 diabetes and compared the performance of different feature selection techniques, including PCA and Lasso, with different machine learning algorithms, including random forest, SVM, and LSTM.…”
Section: Previous Work and Literature Reviewmentioning
confidence: 99%
“…In order to evaluate the effect of the step of feature selection (FS) in improving the accuracy of the predicted glycemia in T1DM subjects, six FS algorithms including LR, RF, Multi-Layer Perceptron (MLP), Instance-Based K-nearest neighbor (IBk), Relief Attribute (Rlf), and PCA beside four predictive algorithms (RF, LR, SVM, and GP) were applied to a biomedical features dataset [ 145 ]. The outcomes showed that RF as both FS technique and predictive algorithm causes the best RMSE (18.54 mg/dL) throughout the 12 considered predictive horizons (up to 60 min in stages of 5 min).…”
Section: The Application Of ML and Dl Models For The Management Predi...mentioning
confidence: 99%